Правова регламентація застосування санітарних та фітосанітарних заходів в Україні у контексті вимог СОТ та ЄС - Духневич, А.; Duhnevych, A. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті висвітлюються питання правової регламентації застосування санітарних та фітосанітарних заходів в Україні у контексті вимог СОТ та ЄС. Здійснено аналіз правової регламентації застосування санітарних та фітосанітарних заходів щодо генетично модифікованих організмів (ГМО). Обгрунтовано положення про те, що у контексті Угоди про санітарні та фітосанітарні заходи СОТ, інших Угод СОТ та Регламентів ЄС, санітарні і фітосанітарні заходи необхідно розглядати як правові положення, закріплені в законах, постановах, правилах, інструкціях та процедурах, включаючи ветеринарні, карантинні та санітарно-епідеміологічні вимоги до кінцевого продукту, до процесу виробництва і обробки продукції, процедури інспектування та сертифікації, направлені на захист життя і здоров'я людей, тварин і рослин. The article highlights the issues of legal regulation of the introduction of sanitary and phytosanitary measures in Ukraine in the context of the requirements of the World Trade Organization (WTO) and the European Union (EU). It is substantiated that in terms of the Agreement on Sanitary and Phytosanitary Measures of the WTO, other WTO Agreements and EU Regulations, sanitary and phytosanitary measures should be considered as legal provisions enshrined in regulatory acts and procedures, including veterinary, quarantine and sanitary-epidemiological requirements concerning the final product, the production process and processing of products, inspection and certification procedures aimed at protecting the lives and health of people, animals and plants. The emphasis is laid on the issues of legal regulation of the application of sanitary and phytosanitary requirements to genetically modified organisms. It is concluded that the norms established therein mainly consort with the Agreement on the Application of Sanitary and Phytosanitary Measures of the WTO, since they eliminate discrimination between WTO members. Nevertheless, most regulations regarging market access, internal support, food security are not in line with the EU regulations and need to be improved by the adoption of a number of new regulatory acts which would regulate these relations in detail.
Legal Regulation of Sanitary and Phytosanitary Measures in Ukraine in the Context of the WTO and the EU Requirements
Keywords: Угода про санітарні та фітосанітарні заходи СОТ; Регламенти ЄС; безпека сільськогосподарської та харчової продукції; генетично модифіковані організми (ГМО); WTO Agreement on Sanitary and Phytosanitary Measures; EU Regulations; Safety of Agricultural and Food Products; Genetically Modified Organisms